Barriers and Challenges of End-of-Life Care Implementation in the Intensive Care Unit: Literature Review - Rizky Meilando; Cecep Eli Kosasih; Etika Emaliyawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: End-of-life care in ICU involves a wide range of staff from every discipline including nurses, who have a lot of interaction time with patients. Most of the patients in the intensive care room have unconscious characteristics and family acts as the holder of autonomy in decision making, so nurses must have competence and experience in caring for patients in the end-of-life phase. However, nurses feel many barriers and challenges in facing the end-of- life in the intensive care environment. This study aimed to identify barriers and challenges of end-of-life care implementation in the ICU Designs: This study used literature review that analyzes articles from five reputable databases such as Pubmed, Proquest, CINAHL, Science Direct, and Google Scholar with the publication year between 2010 - 2021. The keywords used are 'critical care', 'critical care nursing', 'intensive care unit', 'end-of-life care', 'barriers', and 'challenges' with the help of bolean operators 'OR' and 'AND', articles were selected in stages using PRISMA. From the results of 2,186 articles, only 11 articles were identified that met the inclusion and exclusion criteria. Results: The results of the review showed that some barriers of end-of-life care implementation in the ICU are lack of communication, lack of knowledge and training about end of life care, differences in religious and cultural backgrounds, medical team work in the ICU, patient and family factors, and environmental factors. Meanwhile, the challenges of end-of-life care in ICU are communication and decision making in end-of-life care and unrealistic family expectations. Conclusions: There are still many barriers and challenges identified on implementation of end-of-life care in intensive care units, mostly due to lack of knowledge and communication during end-of-life care.  As a recommendation in improving end-of-life care services in the ICU, health service agencies need to increase knowledge and training of health workers about communication and end-of-life care in critical patients.